الأطر المنهجية والنظرية لدراسات "برامج التليفزيون" في المجلات العلمية المحكمة في مصر: دراسة تحليلية - علي، ولاء إبراهيم عقاد Ali, Wala Ibrahim Aqqad (جامعة القاهرة - كلية الإعلام, 2022)
هدفت الدراسة إلى التعرف على الأطر المنهجية والنظرية في بحوث البرامج التليفزيونية المنشورة في المجلات العلمية المحكمة في مصر والمتمثلة في 11 مجلة وذلك بأسلوب الحصر الشامل لتلك الدراسات خلال الفترة ما بين عامي 2013-2020، وخلصت الدراسة في نتائجها إلى ما يلي: 1-تبين ارتفاع عدد دراسات البرامج الحوارية عن عدد دراسات مجالات البرامج التليفزيونية الأخرى المنشورة في المجلات العلمية عينة الدراسة خلال الفترة الزمنية للدراسة الحالية بشكل واضح، كذلك تبين تفوق دراسات البرامج الحوارية على دراسات المجالات البرامجية الأخرى بشكل واضح في (المجلة العلمية لبحوث الإذاعة والتليفزيون بجامعة القاهرة) في المقام الأول. 2-اعتمدت غالبية دراسات برامج التليفزيون في جميع المجلات العلمية عينة الدراسة على منهج المسح الإعلامي بنسبة بلغت 92%. 3-أظهرت النتائج ندرة الاعتماد على أسلوب التحليل الكيفي وحده في تحليل ما توصلت إليه دراسات برامج التليفزيون عينة الدراسة من نتائج، حيث بلغ عدد الدراسات الكيفية في دراسات برامج التليفزيون عينة الدراسة دراستين فقط من إجمالي (122) دراسة. 4-غلب اعتماد دراسات برامج التليفزيون عينة الدراسة على أطر نظرية لاختبار فروضها وتفسير الظواهر موضوع هذه الدراسات، وذلك بنسبة بلغت (67.2%) مقابل نسبة (32.8%) من الدراسات لم تعتمد على أية أطر نظرية في اختبار فروضها وتفسيرها، كما كان أكثرها مداخل تقليدية. The study aimed to identify the methodological and theoretical frameworks in the research of television programs published in the scientific journals courted in Egypt, which consisted of 11 journals, and the study concluded in its results to 1. The increase in the number of studies of talk shows on the number of studies of other areas of television programs published in scientific journals showed a sample of the study during the time period of the current study clearly, as well as showing that the studies of talk shows are clearly superior to the studies of other programmatic fields in (Scientific Journal of Radio and Television Research at Cairo University) in the first place. 2- The majority of television programme studies in all scientific journals relied on the sample of the study on the media survey curriculum by a percentage of (92.6%). The results showed a dearth of reliance on the method of qualitative analysis alone in the analysis of the results of the television programme studies sample the study, where the number of qualitative studies in the studies of television programs sample study only two studies out of a total (122) studies. 5- The adoption of television program studies dominated the sample of the study on theoretical frameworks to test their assumptions and interpret the phenomena subject of these studies, by a percentage of (67.2%) compared to 32.8% of studies did not rely on any theoretical frameworks in testing and interpreting their assumptions, as were the most traditional entries.
Keywords: وسائل الإعلام -- البرامج التليفزيونية -- مصر